2020
DOI: 10.1021/acs.iecr.0c02211
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Supported Copper Catalysts for Oxidative Degradation of Phenolics in Aqueous Medium: Optimization of Reaction Conditions, Kinetics, Catalyst Stability, Characterization, and Reusability

Abstract: Catalytic wet oxidation (CWO) of phenolic wastewater containing phenol, o-cresol, and 2,5-dimethylphenol was carried out in a batch reactor (phenolics = 10 g/L, chemical oxygen demand (COD) = 26 000 mg/L, and total organic carbon (TOC) = 7900 mg/L). Using the Box–Behnken experimental design (BBD) approach, the following optimum CWO conditions (catalyst: 5% Cu/AC) for phenolics degradation were found: C cat = 3.4 g/L, T = 148 °C, P O2 = 0.61 MPa, and pH = 7.4. Under these conditions, TOC and COD removals of 88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…An activated carbon (AC)-supported Cu catalyst was developed for CWO of phenolic wastewater containing phenol, o-cresol, and 2,5-dimethylphenol in a batch reactor. 34 It was found that TOC and COD removal were found to be 88 and 90%, respectively, using the Cu (5 wt %)/AC catalyst at 148 °C temperature, 0.61 MPa oxygen pressure, pH = 7.4, 3.4 g/L catalyst dosage, and 4 h reaction duration. Some reaction intermediates were identified such as carboxylic acids, pbenzoquinone, and hydroquinone.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…An activated carbon (AC)-supported Cu catalyst was developed for CWO of phenolic wastewater containing phenol, o-cresol, and 2,5-dimethylphenol in a batch reactor. 34 It was found that TOC and COD removal were found to be 88 and 90%, respectively, using the Cu (5 wt %)/AC catalyst at 148 °C temperature, 0.61 MPa oxygen pressure, pH = 7.4, 3.4 g/L catalyst dosage, and 4 h reaction duration. Some reaction intermediates were identified such as carboxylic acids, pbenzoquinone, and hydroquinone.…”
Section: Introductionmentioning
confidence: 96%
“…There are various existing methods that can be used to remove phenol and its derivatives from wastewater . Among the various methods, the most commonly used methods to remove phenol and phenol derivatives are advanced oxidation processes (AOPs), such as photocatalytic oxidation, photoelectron catalytic degradation, sonocatalytic degradation, , Fenton reaction by using H 2 O 2 , O 3 , or other oxidizing agents. All these methods are effective in treating wastewater containing phenol and phenol derivatives, but these methods are high energy-consuming methods and need high cost. Recently, catalytic wet air oxidation (CWAO) has attracted much attention for the treatment of phenol because of its high versatility and remarkable economy-scale advantages. CWAO is an ecofriendly process because air and/or oxygen are used directly as the oxidant instead of the harmful ozone or expensive H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diverse literature is available for the treatment of toxic compounds in aqueous solution using CWAO alone. Wang et al studied the oxidation of chlorobenzene contained in humid air using Ru-coated Pt dimers on the γ-Al 2 O 3 surface and obtained ∼98% conversion for 600 min at 200 °C from a feed stream containing 167 mg/L chlorobenzene . Gutiérrez-Sánchez et al studied the degradation of ciprofloxacin in aqueous solution using sewage sludge-derived activated carbon (SAC) loaded with iron nanoparticles and reported 99% ciprofloxacin degradation (initial concentration 50 mg/L) within 2 h at 140 °C and 20 bar (air pressure) with a catalyst dosage of 0.7 g/L .…”
Section: Introductionmentioning
confidence: 99%